Be smart online - Atkins, Marcie Flinchum (2019)
"Introduces the reader on how to navigate through online."--
Your digital footprint -- Passwords and privacy -- Be smart about downloads -- Digital citizenship -- Activity #1: Spot the problem -- Activity #2: Digital decisions quiz.
Includes index.
Keywords: Internet and children -- Juvenile literature; Internet -- Safety measures -- Juvenile literature; Online social networks -- Safety measures -- Juvenile literature